Cytochrome P-450 CYP2C19 genetic polymorphism and its relation with clopidogrel resistance - Usman Nawaz; Mudassar Noor; Akbar Waheed (Journal of the Pakistan Medical Association, 2023)
Objectives: To find out the prevalence of CYP2C19*2 genetic polymorphism in ischemic heart disease patients, and to determine its relation with clopidogrel resistance in different genotype groups. Method: The cross-sectional study was conducted from August 2015 to December 2019 at the Army Medical College, National University of Medical Sciences, Rawalpindi, Pakistan, and comprised ischemic heart disease patients of either gender who were on clopidogrel therapy. CYP2C19*2 genotyping of all the patients was carried out through polymerase chain reaction-restriction fragment length polymorphism. Platelet aggregation analysis was done using a light transmission aggregometer. Data was analysed using SPSS 23. Results: Of the 390 patients, 232(59.5%) were males and 158(40.5%) were females. The overall age range was 16-82 years. Clinical indications of clopidogrel were angina 198(50.8%), myocardial infarction 146(37.4%) and acute coronary syndrome 46(11.8%). CYP2C19*2 genotyping showed that 196(50.24%) patients were homozygous wild type carriers (GG or *1/*1), 159(40.8%) were heterozygous carriers (GA or *1/*2), and 35(9%) were homozygous polymorphic allele carriers (AA or *2/*2). Platelet aggregation studies showed that there were 157(80.1%) clopidogrel responders and 39(19.9%) clopidogrel-resistant patients among GG carriers, 118(74.2%) clopidogrel responders and 41(25.8%) clopidogrel-resistant among GA carriers, and 18(51.4%) clopidogrel responders and 17(48.6%) clopidogrel-resistant among AA carriers (p=0.001). Intergroup mean platelet aggregation was significantly different (p=0.025). Allelic frequency of dominant allele *1 and polymorphic variant allele *2 was 0.706(70.6%) and 0.294(29.4), respectively. Conclusion: Homozygous and heterozygous carriers of CYP2C19 allele *2 was found to have higher prevalence of clopidogrel resistance in the studied population. Key Words: CYP2C19, Genetic polymorphism, Clopidogrel.